Hysterosalpingography and Ultrasonography Features of Herlyn-Werner-Wunderlich Syndrome Detected during Infertility Workup - Hidayatullah Hamidi; Bibi Hosai Balkhi (Case Reports in Radiology)
The Herlyn-Werner-Wunderlich syndrome (HWWS) is a very rare congenital anomaly of the urogenital tract. It is characterized by a combination of didelphys uterus, unilateral vaginal obstruction, and ipsilateral renal agenesis. MRI imaging is usually used for diagnosis; however, the authors present a case of HWWS diagnosed by ultrasonography (HSG) and hysterosalpingography (HSG) in a 22-year-old lady who has undergone an imaging workup of infertility.